Public Relations Strategy of Magdalene Online Media in Shaping Public Awareness of #MendobrakBias Campaign - Zinda Adinta Sari; Ninis Agustini Damayani; Yanti Setianti (Ultimacomm: Jurnal Ilmu Komunikasi, 2022)
The existence of online media in the 5.0 era as it is today is considered as one of the vital components. In the spreading of the flow accurate information, without knowing the limitations of distance and time. In this current digital era, the Public Relations strategy that implied in social media is very crucial. In function to shaping public awareness which related to certain issues. Online media can unwittingly become a space for advocacy practice in the public sphere, as well as Magdalene which focuses on women’s advocacy efforts through its content as an alternative media. This study uses a qualitative approach, with constructivist paradigm, and a case study approach. This study shows the implied PR strategy which Magdalene uses in shaping public awareness of #MendobrakBias campaign in order to celebrated International Women’s Day on March 8th 2022. One of the strategies implied from the way of Magdalene produce and published the issue, which never published on mainstream media, and the content publication through social media which are packaged in an attractive and contemporary ways, conducting online discussions with the community. So, it makes the public is more aware of #MendobrakBias campaign. Keywords: Public Relations, Strategy, Public Awareness, Campaign, Women’s Advocacy